Adapting a Low-threshold Buprenorphine Program for Vulnerable Populations During the COVID-19 Pandemic. Issue 5 (September 2021) - Nordeck, Courtney D.; Buresh, Megan; Krawczyk, Noa; Fingerhood, Michael; Agus, Deborah
Abstract : Objectives: To examine patient characteristics and outcomes among opioid use disorder patients enrolled in low-threshold buprenorphine treatment during the COVID-19 pandemic. Methods: This paper describes the adaptation of the Project Connections (PC) program, a low-threshold buprenorphine program in Baltimore, in response to the COVID-19 pandemic. This paper examines patient characteristics and initial outcomes of patients served during a rapid protocol shift to telehealth that allowed buprenorphine initiation without an in-person encounter following a state-mandated stay-at-home order. Patient characteristics were compared to a subsample of patients enrolled in the program before the COVID-19 pandemic. Results: In March 2020, there was a sharp increase in new enrollments to the PC program. A total of 143 patients completed an intake assessment between March and May 2020 and 140 began treatment with buprenorphine/naloxone. Those who completed an intake assessment were primarily male (68.5%), Black (83.2%), had a mean age of 43.2 years (SD = 11.7), and reported a mean of 17.0 years of opioid use (SD = 12.9). The majority of patients were unemployed (72.7%) and reported previous criminal justice involvement (69.2%). Of those who completed an intake assessment, 96.5% returned for a second visit. Among those for whom 30-day retention data was available (n = 113), 63.7% were engaged for 30 days or longer. Conclusions: The PC program illustrates that offering on-demand, flexible treatment is an opportunity to increase opioid use disorder treatment access, even during a public health emergency that disrupted access to services. Relaxation of buprenorphine telehealth regulations allowed for flexibility in treatment and benefits vulnerable populations.